Limpet shell modifications at intertidal hydrothermal vents - Couto,Ruben P. (2012)
Calcareous organisms are known to be sensitive to acidified seawater, and they have been reported as potential sentinels for ocean acidification studies. Limpets are among the organisms that characterise intertidal zones, and in the Azores can also be found at sites with shallow water hydrothermal activity, where the acidity of seawater in the vicinity of hydrothermal vents is naturally higher due to CO2 release. During an occasional intertidal survey on the occurrence and abundance of intertidal algae we found limpets with abnormal shells, and specimens of Patella candei gomesii (Patellidae) collected under such conditions exhibited weak and almost transparent shells with reduced shell thickness.